2003
DOI: 10.1093/fampra/20.2.103
|View full text |Cite
|
Sign up to set email alerts
|

What is the predictive value of urinary symptoms for diagnosing urinary tract infection in women?

Abstract: In women with urinary symptoms, a thorough clinical examination, together with performance of a reactive strip test during the office visit, improves the chances of detecting UTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 9 publications
5
31
1
Order By: Relevance
“…An epidemiologic study from Spain involving 343 women aged 14 to 90 years showed that pretest probability of having a UTI among patients with new urinary symptoms was 0.48; positive likelihood ratio (LR) for new dysuria was 1.31 (95% CI, 1.12–1.54), new urgency 1.29 (95% CI, 1.12–1.50), and new urinary frequency 1.16 (95% CI, 1.06–1.28). 35 This study reinforces the notion that new dysuria is the most discriminating clinical finding for symptomatic UTI. When evaluating new dysuria, timing, severity, and location are important.…”
Section: The Evidence: Diagnosis Management and Preventionsupporting
confidence: 88%
“…An epidemiologic study from Spain involving 343 women aged 14 to 90 years showed that pretest probability of having a UTI among patients with new urinary symptoms was 0.48; positive likelihood ratio (LR) for new dysuria was 1.31 (95% CI, 1.12–1.54), new urgency 1.29 (95% CI, 1.12–1.50), and new urinary frequency 1.16 (95% CI, 1.06–1.28). 35 This study reinforces the notion that new dysuria is the most discriminating clinical finding for symptomatic UTI. When evaluating new dysuria, timing, severity, and location are important.…”
Section: The Evidence: Diagnosis Management and Preventionsupporting
confidence: 88%
“…Most of these diagnostic indicators have been studied in single-test evaluations, implying that a test is compared with the urine culture without taking into account the results of preceding tests, including clinical history. [16][17][18][19] In clinical practice, however, the diagnostic work-up is multivariable, and test results are mutually dependent. [20][21][22][23][24] For example, the diagnostic value of the dipslide used in isolation may be considerable, but it might not add much once the clinical history and nitrite test result are known.…”
Section: Diagnosing Acu T E Unco Mpl Ic At Ed U T Imentioning
confidence: 99%
“…The second screening (of full-text articles) revealed eight studies [14,18-23,26,28] that satisfied the inclusion criteria. Three additional articles were cited in reviews or in the references of other articles and were subsequently included in our study [24,25,27] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%